Feminist Perspective in Laleh Bakhtiar’s Translation of the Holy Qur’ān - Bokhari, Dr. Abida; Jawaid, Dr. Sadia Jawaid (Al-Amīr Research Journal for Islamic Studies, 2023)
For almost fourteen centuries, Muslims have believed that lightly beating one’s disobedient wife is a permissible act in Islam and is based on Qur’ānic verse 4:34. Various interpretations of this verse have caused a great deal of controversy among scholars. Recently, some modern scholars and feminists have also tried to come up with a modern interpretation of this verse. According to the Islamic feminist group, the text of this verse is used by Muslim men as an excuse for domestic violence. Laleh Bakhtiar, who translated the Qur’ān into English, has been criticized for interpreting the verse in the same way as feminists, while Bakhtiar does not accept the criticism. The purpose of this article is to find out whether Bakhtiar’s gender influences her translation. Especially how she translates verse 4:34 of the Holy Qur’ān. Does she adopt a feminist approach to the interpretation of this verse? Keywords: Holy Qur’ān, Translation, Laleh Bakhtiar, Feminist, Gender equality, Wife-Beating.